Retrospective Review of Immediate Restoration of Lordosis in Single-Level Minimally Invasive Transforaminal Lumbar Interbody Fusion: A Comparison of Static and Expandable Interbody Cages. Issue 5 (23rd August 2019) - Vaishnav, Avani S; Saville, Philip; McAnany, Steven; Kirnaz, Sertac; Wipplinger, Christoph; Navarro-Ramirez, Rodrigo; Hartl, Roger; Yang, Jingyan; Gang, Catherine Himo; Qureshi, Sheeraz A
Abstract: BACKGROUND: Sagittal alignment is an important consideration in spine surgery. The literature is conflicted regarding the effect of minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) on sagittal parameters and the role of expandable cage technology. OBJECTIVE: To compare lordosis generated by static and expandable cages and to determine what factors affect postoperative sagittal parameters. METHODS: Preoperative regional lordosis (RL), segmental lordosis (SL), and posterior disc height (PDH) were compared to postoperative values in single-level MI-TLIF performed using expandable or static cages. Patients were stratified based on preoperative SL: low lordosis (<15 degrees), moderate lordosis (15-25 degrees), and high lordosis (>25 degrees). Regression analyses were conducted to determine factors associated with postoperative SL and PDH. RESULTS: Of the 171 patients included, 111 were in the static and 60 in the expandable cohorts. Patients with low preoperative lordosis experienced an increase in SL and maintained RL regardless of cage type. Those with moderate to high preoperative lordosis experienced a decrease in SL and RL with the static cage, but maintained SL and RL with the expandable cage. Although both cohorts showed an increase in PDH, the increase in the expandable cohort was greater. Preoperative SL was predictive of postoperative SL; preoperative SL, preoperative PDH, and cage type were predictive of postoperative PDH. CONCLUSION: Expandable cages showed favorable results in restoring disc height and maintaining lordosis in the immediate postoperative period. Preoperative SL was the most significant predictor of postoperative SL. Thus, preoperative radiographic parameters and goals of surgery should be important considerations in surgical planning. Graphical Abstract: